A Review on Recent Developments in Deuteron Induced Reactions Enhancing NRA Capabilities - Kokkoris, M.; Misaelides, P.; Lagoyannis, A.; Vlastou, R.; Papadopoulos, C. T.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2020)
Nuclear Reaction Analysis (NRA) is well established as one of the principal IBA methods nowadays. Among the most important NRA characteristics are its high iso- topic selectivity, its enhanced sensitivity for many nuclides, the capability of least destructive depth profiling and the possibility of simultaneous analysis of more than one light element in near–surface layers of materials. Moreover, in the particular case when deuterium is used as probing beam, critical advantages for NRA studies emerge. As NRA quantifies individual light isotopes absolutely, and can depth pro- file with nanometer resolution, it is the most suitable ion beam technique for the determination of the concentration and depth profiling of light elements in complex matrices. However, as already pointed out in the recent literature, the application of NRA to the determination of the concentration and the depth profiling of light elements is frequently impeded by the lack of adequate and/or reliable experimental differential cross section data. It is the ambition of the present work to contribute in the fields of differential cross section measurements, as well as of data evaluation and general theoretical analysis.